Applied deep learning and computer vision for self-driving cars : build autonomous vehicles using deep neural networks and behavior-cloning techniques - Ranjan, Sumit; Senthamilarasu, S. (Packt Publishing, 2020)
This book teaches you the different techniques and methodologies associated while implementing deep learning solutions in self-driving cars. You will use real-world examples to implement various neural network architectures to develop your own autonomous and automated vehicle using the Python environment.
Table of ContentsThe Foundation of Self-Driving CarsDive Deep into Deep Neural NetworksImplementing a Deep Learning Model using KerasComputer Vision for Self-Driving CarsFinding Road Markings using OpenCVImproving the Image Classifier with CNNRoad Sign Detection using Deep LearningThe Principles and Foundations of Semantic SegmentationImplementation of Semantic SegmentationBehavior Cloning using Deep LearningVehicle Detection using OpenCV and Deep LearningNext Steps.
Keywords: Automated vehicles -- Computer simulation.; Machine learning.; Neural networks (Computer science); elektronické knihy; electronic books